Listening to Old Woman speak : Natives and alterNatives in Canadian literature - Groening, Laura, 1949- (McGill-Queen's native and northern series, 2004)
"While Canadian First Nations writers have long argued that non-Native authors should stop appropriating Native voices, many non-Native writers have held that such a request constitutes censorship. "Listening to Old Woman Speak" provides the historical context missing from this debate. Laura Groening examines issues of gender and genre, historical fiction and historical metafiction, and postcolonial theory to provide compelling evidence that it is virtually impossible to escape one's own cultural conditioning. She concludes by "listening" to what First Nations writers have to say about cultural identity and the need to establish a healing aesthetic